Penyusunan Profil Wilayah Kadus III di Desa Ceporan, Kecamatan Gantiwarno, Kabupaten Klaten ditinjau dari Aspek Fisik - Amithya Irma Kurniawati; Dwi Kunto Nurkukuh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
The problem faced by partners is the unavailability of profiles that explain the physical conditions found in the Hamlet Head (Kadus) III regional and the conditions have not been uploaded to the Ceporan Village website. The purpose of this community service is to do profiling of Kadus III regional profiles in Ceporan Village from a physical aspect. This community service uses documentation examination and interview techniques. Examination of documentation is necessary to obtain the physical conditions found in the Kadus III regional in Ceporan Village. Interview techniques are needed to obtain updates on the physical conditions found in the Kadus III regional in Ceporan Village. The results of this community service consist of two (2) parts, namely: the physical condition of the Ceporan Village and Kadus III regional. The physical conditions of the Ceporan Village regional, including: general description and land use of the regional. The physical conditions of the Kadus III regional, including: physical conditions in Tegal Gaswangi, Gamelan, Brambangan, Ceporan, Karang Nongko, and Kulungan hamlets. The physical conditions are uploaded to the Ceporan Village website.